A Comment on "An Experimental Manipulation of the Value of Effort" - Robin Brooker; Sergio Lo Iacono (Institute for Replication (I4R), 2025)
Lin et al. (2024) investigates the effect of rewarding effort on task preferences in adult participants using a mixed-design experiment with Bayesian linear regression models. The aim was to recognise whether rewarding effort increases individuals' willingness to choose effortful (harder) tasks and whether this effect persists beyond incentivised contexts. The authors find limited evidence that rewarding effort increases people's willingness to choose more effort task when rewards are no longer offered. Moreover, the authors present mixed-evidence that incentivising effort increased willingness to choose more effortful tasks in a separate unrelated and unrewarded task. We successfully computationally reproduce the main claims of the paper (hypotheses 1-8), but uncover some minor typographical/rounding errors in presentation of the confidence intervals. We further test the robustness of the results to different priors in Bayesian Regression Models using Stan, increasing the number of iterations and independent chains to estimate posterior parameters. Results are robust to these changes to model specification.
Keywords: 330